A Non-Linear Relationship between Working Capital Management and Firm Profitability: Evidence from Manufacturing Companies Listed on LSE - Aslanova, Elvira (2015)
Purpose: The purpose of the current study is to analyse the relationship between working capital management (WCM) efficiency and firm profitability for a sample of manufacturing firms listed on London Stock Exchange (LSE). Methodology/ Approach: The study adopts a quantitative approach on a sample of 79 manufacturing firms from four different industries, namely Electronic & Electrical Equipment, Food & Beverage, Chemicals and Pharmaceuticals. The data is gathered with the access to financial statements of the listed companies from BLOOMBERG database covering a period of 10 years from 2005 to 2014. Days of inventory outstanding (DIO), days of sales outstanding (DSO), and days of payables outstanding (DPO) have been used as explanatory variables. Ratio Analysis, Pairwise Correlation Matrix and Panel Data Analysis are implemented in the paper. Findings: Fixed Effect estimation techniques reveal that corporate performance can be improved by efficient management of working capital. Moreover, the paper finds a non-linear relationship between firm profitability, measured through return on sales (ROS) and explanatory variables. There is also a positive relationship between the profitability levels and control variables, such as size and sales growth. A statistically significant negative coefficient for the Current Ratio indicates the inverse relationship between corporate profitability and liquidity, implying the necessity of proper management of both. Originality: To the best of my knowledge, this is the first study to reveal a non-linear relationship between firm profitability and determinants of working capital management such as DIO, DSO, and DPO.